Influence of Pulsed Electric Fields processing at high-intensity electric field strength on the relationship between anthocyanins composition and colour intensity of Merlot (Vitis vinifera L.) musts during cold maceration. (January 2020) - Leong, Sze Ying; Treadwell, Meghan; Liu, Tingting; Hochberg, Martin; Sack, Martin; Mueller, Georg; Sigler, Juergen; Silcock, Patrick; Oey, Indrawati
Abstract: Merlot grapes have high proportion of anthocyanins protected inside cell vacuoles but the thick skins limit their extractability. This study investigated the effect of a continuous Pulsed Electric Fields (PEF at 500 kg/h) system operated at high-intensity electric field strengths (>30 kV/cm) combined with energy inputs ranging from 4.7 to 49.4 kJ/L on anthocyanins extraction and colour intensity of Merlot musts during a 4-day cold maceration. Considerable amount of anthocyanins with different chemical features was extracted instantaneously due to PEF treatment at high-intensity electric field strength, in which the amount was higher than those extracted from non PEF-treated Merlot followed by 4 days maceration. During maceration, malvidin derivatives were the most significant anthocyanins contributing ( r > 0.71, p < 0.05) to the changes in colour intensity of PEF-treated musts. This finding suggests that malvidin derivatives are good indicators to predict the efficiency of specific PEF process condition in reducing the length of cold maceration while achieving maximum colour intensity in the musts. This research is important either for the wine and beverage industries. Industrial relevance text: Previous PEF studies mainly investigated the effect of low-intensity electric field strength (<7 kV/cm) on various grapevine varieties, the current study investigated the effect of PEF on grapes at high-intensity electric field strength (>30 kV/cm) using Marx generator for the first time in the literature. Marx generator has a tendency to produce high-intensity electric field strength, up to 80 kV/cm, but the impact on plant materials intended for food application are not well studied. In this study, Merlot grapes were continuously treated with PEF at high-intensity electric field strength at a flow rate of 500 kg/h while many previous studies conducted trial at approximately 100–200 kg/h in conjunction with low-intensity electric field strength (<7 kV/cm). Therefore, it seems necessary to advance the current application of PEF for grape processing to high-intensity electric field strength in order to cope with or fit into the standard production rate (>200 kg/h) at the commercial scale. In this study, we have successfully showed that high-intensity electric field strengths (33.1 and 41.5 kV/cm) of PEF were efficient (i.e. instantaneous extraction) in extracting all types of anthocyanins with different chemical features from the thick-grape skins of Merlot. Therefore, grape juice with more elaborated anthocyanin composition and intense colour was produced at a large scale immediately after PEF. The extracted anthocyanins were found to be stable over time after PEF treatment in which the issues on anthocyanin stability and colour development have never been considered in many previous studies, but are important quality aspects that beverage industry desired. Highlights: High-intensity electric field strength >30 kV/cm was tested on Merlot grapes. PEF instantaneously extracted a variety of anthocyanins from Merlot skins. PEF reduced the cold maceration time for maximal anthocyanin extraction. Malvidin extracted from PEF-treated Merlot contributed to the intense musts colour.